Bug Bounty Hunting: A Case Study of Successful Vulnerability Discovery and Disclosure - Elan Maulani, Isma; Anggraeni, Riska (Devotion : Journal of Research and Community Service, 2023)
This research is a case study on bug bounty hunting as a successful approach to finding and uncovering vulnerabilities in software. The purpose of this study is to understand the effectiveness of bug bounty hunting and its benefits in improving company security. Qualitative research methods were used by analyzing data from bug bounty programs that were successful in finding significant vulnerabilities. The results showed that bug bounty hunting proved to be effective in capturing various types of vulnerabilities, including web application vulnerabilities, network protocol vulnerabilities, hardware security vulnerabilities, and mobile app vulnerabilities. Security researchers play a critical role in the success of the bug bounty hunt, with their expertise in bug hunting and deep understanding of the technology. The benefits of bug bounty hunting include increased software security, cost efficiency, and increased company reputation for security and credibility. However, challenges such as finding hidden vulnerabilities and coordinating with enterprises need to be overcome. Recommendations include strengthening collaboration between enterprises and security researchers, establishing effective communication channels, and proactively responding to vulnerability reports.